Comparison of residual stress on different three-dimensional multi-layer welding methods of welded hollow sphere joint in large-span structure by considering latent heat. Issue 3 (September 2019) - Ri, Nam-Hyok; Chen, Zhihua; Ri, Yong-Sop; Ma, Zhiyao
This article quantitatively evaluated the influence of three-dimensional multi-layer welding on the welding residual stress of super-big diameter welded hollow sphere joint in the large-span spatial steel structure considering the influence of material state change using finite element method. First, this article proposed a conception of equivalent state change time—the virtual time of state change in the analysis of welding and cooling—which represents the heat absorbed or released during the change of solid and fluid states in welding material. The equivalent state change time increases the accuracy of the thermal analysis considering the latent heat of fusion in welding and cooling process. Second, this article simulated the numerical experiments of three welding methods including multi-layer symmetric welding, multi-layer sequential welding, and single-layer symmetric welding, which show that multi-layer symmetric welding not only increases the balance of supporting ability of structure but also decreases the value of maximum tensile residual stress, and it is better than the other two welding methods.